PERAN KEGIATAN KEAGAMAAN DALAM MENINGKATKAN KUALITAS PEMBELAJARAN DI PONDOK PESANTREN QUR'AN MARKAZ IMAM MALIK - Nurung, Muh; Indri Karadona, Rosika; Puspita Sari, Arni (SEMAR : Jurnal Sosial dan Pengabdian Masyarakat, 2025)
This study aims to evaluate and improve the effectiveness of religious activities at Qur’an Islamic Boarding School Markaz Imam Malik, focusing on Weekly Taklim and Tajwid Halaqah as platforms for student learning and character development. The method employed is Participatory Action Research (PAR), involving all elements of the pesantren in the planning, implementation, and evaluation of programs. The findings show that Weekly Taklim significantly enhances students' Islamic understanding, character building, and critical thinking skills through the use of sorogan, bandongan, question-and-answer, and group discussion methods. Meanwhile, the Tajwid Halaqah, using talaqqi, musyafahah, sorogan, and tikrar methods, proves effective in improving the accuracy of Qur’anic recitation and fostering students' spiritual development. Challenges include time limitations, varying student capabilities, and a lack of qualified teachers with authentic sanad. Overall, the religious activities at this pesantren play a strategic role in nurturing students who excel spiritually, intellectually, and socially.